Suppose that $ G $ is a function of the underlying asset $ S $, which follows a geometric Brownian motion. Suppose that $ \sigma_{S} $ and $ \sigma_{G} $ are the volatilities of $ S $ and $ G $, respectively. Show that if $ \mu $, the rate of return of $ S $, increases by a constant $ \lambda $, then the rate of return of $ G $ increases by $\lambda \frac{\sigma_{G}}{\sigma_{S}} $.

This is my answer:

Since $S$ follows a geometric brownian motion:

$$dS_{t}=\mu_{S} S_{t}dt + \sigma_{S} S_{t}dW_{t}$$

Using Ito for the function $G(s)$ we get:

$$dG(S_{t})=G^{'}(S_{t})dS_{t} + \frac{1}{2}G^{''}(S_{t})S_{t}^{2}\sigma^{2}_{S}dt$$

$$=G^{'}(S_{t})(\sigma_{S} S_{t}dW_{t} + \mu_{S} S_{t}dt) - \frac{1}{2}G^{''}(S_{t})S_{t}^{2}\sigma_{S}^{2}dt$$

$$=G^{'}(S_{t})\sigma_{S} S_{t}dW_{t} + (\mu_{S} S_{t}G^{'}(S_{t}) - \frac{1}{2}G^{''}(S_{t})S_{t}^{2}\sigma_{S}^{2})dt$$

When $\mu_{S}$ increases by a constant $\lambda$

$$(\mu_{S}+\lambda) S_{t}G^{'}(S_{t}) - \frac{1}{2}G^{''}(S_{t})S_{t}^{2}\sigma_{S}^{2}=\mu_{S} S_{t}G^{'}(S_{t}) + \lambda S_{t}G^{'}(S_{t}) - \frac{1}{2}G^{''}(S_{t})S_{t}^{2}\sigma_{S}^{2}$$

\Rightarrow $\mu_{G}$ increases by $\lambda S_{t}G^{'}(S_{t})=\lambda \frac{\sigma_{G}}{\sigma_{S}}$

Is this ok?


What you've written looks comprehensible. What is missing is the definition of $\sigma_G \equiv \sigma_G(S_t,t)$, i.e.

Let $\sigma_G\equiv \sigma_S S \frac{\partial G(S_t,t)}{\partial S_t}$

  • $\begingroup$ The problem doesnt say that. Can I assume that is $\sigma_{G}$? $\endgroup$ Dec 7 '20 at 16:04
  • $\begingroup$ Is there another way of answering the question? $\endgroup$ Dec 7 '20 at 16:08
  • $\begingroup$ I think you can say that, yes. $\endgroup$ Dec 7 '20 at 16:52

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.